UAE High School Students' Attitude Towards Traditional and Computer-Mediated Peer Response - Al Arini, Muntaha Mohammad (2010)
A Master of Arts Thesis in Teaching English to Speakers of Other Languages (TESOL) by Muntaha Mohammad Al Arini Entitled, "UAE High School Students' Attitude Towards Traditional and Computer-Mediated Peer Response," August 2010. Available are both Hard and Soft Copies of the Thesis.